2020
DOI: 10.2174/1567205016666191210091302
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Calcium Signaling as a Therapeutic Target for Alzheimer’s Disease

Abstract: Mitochondria absorb calcium (Ca2+) at the expense of the electrochemical gradient generated during respiration. The influx of Ca2+ into the mitochondrial matrix helps maintain metabolic function and results in increased cytosolic Ca2+ during intracellular Ca2+ signaling. Mitochondrial Ca2+ homeostasis is tightly regulated by proteins located in the inner and outer mitochondrial membranes and by the cross-talk with endoplasmic reticulum Ca2+ signals. Increasing evidence indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 176 publications
0
7
0
1
Order By: Relevance
“…The hippocampus is severely affected in diseases with neuroinflammatory components such as AD [ 14 ]. Significant memory loss and cognitive decline are associated with neuronal death and gray matter loss, especially in the frontal cortex and hippocampus [ 84 ]. The destruction of neuronal homeostasis determines irreversible degeneration and neuronal apoptosis.…”
Section: Ad Relation To the Cholinergic Systemmentioning
confidence: 99%
“…The hippocampus is severely affected in diseases with neuroinflammatory components such as AD [ 14 ]. Significant memory loss and cognitive decline are associated with neuronal death and gray matter loss, especially in the frontal cortex and hippocampus [ 84 ]. The destruction of neuronal homeostasis determines irreversible degeneration and neuronal apoptosis.…”
Section: Ad Relation To the Cholinergic Systemmentioning
confidence: 99%
“…Calcium overload can activate calcium-dependent proteases and nitric oxide synthase, destroy mitochondria, and result in neuronal excitotoxicity. , These effects might derive from the formation of ion channels within the cell membrane by toxic fragments of fibril Aβ, fostering a direct leakage of calcium into cells . Some studies have shown that several L-type calcium channel blockers may alleviate neuronal degeneration in early-stage AD therapy. , Therefore, in the above-mentioned mechanism investigation, the falcarinol-type analogues might act as targeted molecules for L-type calcium ion channels and play a blocking role in the upstream of the cell pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Mitochondria absorb Ca 2+ at the expense of the electrochemical gradient generated during respiration. Mitochondrial Ca 2+ overload means high uptake of mitochondrial Ca 2+ which makes it easier to impair neuron functions and exacerbates AD progression by impairing mitochondrial respiration, increasing reactive oxygen species formation, inducing apoptosis, and damaging mitochondria recycling mitophagy ( Wu et al, 2020 ). Mitochondria are essential energy generators for tissue homeostasis and channels for programmed apoptosis and necrotic cell death.…”
Section: Introductionmentioning
confidence: 99%